STRATEGI PELATIHAN PENGUATAN EKONOMI UMKM: MENGATASI TANTANGAN PENGEMBANGAN DESA WISATA CIDERUM, BOGOR - Imam Ardiansyah; Yudhiet Fajar Dewantara; Ika Suryono Djunaid; Dewanta Facrureza; Prayogo Susanto; Antonius Rizki Krisnadi; Vishnuvardhana Vishnuvardhana (LP2M Universitas Ibrahimy, 2023)
This study aims to thoroughly assess the effectiveness of a training program in enhancing the economic prospects of the Micro, Small, and Medium Enterprises (UMKM) sector within the picturesque village of Desa Wisata Ciderum, located in Bogor. The research methodology employed here utilizes a comprehensive case study approach, centering on 25 UMKM practitioners who actively participated in a training program focusing on competency development and digital marketing strategies. Data were meticulously gathered through a combination of in-depth interviews and careful observations. Subsequently, a qualitative approach was employed to meticulously analyze the amassed data. The findings unequivocally demonstrated that the training program wielded a significantly positive influence. It led to substantial increases in sales figures, a notable expansion in market reach, and a remarkable enhancement of UMKM brand recognition within the community and beyond. Furthermore, this training initiative proved to be an effective solution in addressing the existing challenges related to limited knowledge and skills within the UMKM sector. It also played a pivotal role in fostering collaborative partnerships among the UMKM practitioners. The conclusions drawn from this research are of paramount importance, offering invaluable insights into the economic development of Desa Wisata Ciderum. By employing effective and sustainable training approaches, this study underscores the potential for further strengthening the UMKM sector, thereby contributing to the overall prosperity of the village.